Pengaruh Media Kotak Angka Berbasis Sensor Audio terhadap Pemahaman Konsep Dasar Angka pada Anak Down Syndrome Kelas III - Angelina Putri Wijaya; Lailil Aflahkul Yaum; Sugihartatik Sugihartatik (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the effect of audio-sensor-based number box media on the understanding of basic number concepts in third-grade children with Down syndrome at SLB Negeri 1, Blitar City. The method used was a Single Subject Research (SSR) with an A-B design, consisting of a Baseline (A) and an intervention (B) phase. The results showed a significant increase in ability from 28.57% - 35.71% in the baseline phase to 42.86% - 92.86% in the intervention phase, with 0% overlap. The conclusion is that audio-sensor-based number box media is effective in improving understanding of basic number concepts through a multisensory approach (visual, auditory, kinesthetic, and tactile). Keywords: Down Syndrome, Number Concepts, Multisensory Media, Audio Sensors, SSR